Peningkatan Kemampuan Mengaji melalui Pelatihan Qira’ah 7 Nada di Desa Palrejo Sumobito Jombang - Khotim Fadhli; Akhmad Taqiyuddin; Afif Kholisun Nasohih; Aisya Naila Syarifah; Mochammad Anas; Ahmad Muqoffy; Mukhamad Rizza Mahdani; Nisa Ul Afiyah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2026)
The Qur’an encompasses both spiritual and aesthetic dimensions, one of which is manifested through the art of Qira’ah. However, the current phenomenon shows that many young generations are only able to read the Qur’an technically without mastering the variations of Qira’ah tones, making the recitation sound monotonous and less engaging. This condition is also found in Palrejo Village, Sumobito Subdistrict, Jombang Regency, where although competent qaris and qari’ahs exist, structured training platforms for children and youth remain limited. To address this need, a Rapid Training of Qira’ah Seven Tones was implemented using a participatory approach that involved students, teachers, and community leaders. The program was attended by 27 participants from three local TPQs, applying lectures, demonstration, visual aids, hands-on practice, and reinforcement through digital media in the form of QR codes containing recorded materials. Evaluation results indicate an improvement in participants’ skills in reciting the Qur’an with tonal variations, development of vocal and breathing techniques, as well as enhanced self-confidence. Furthermore, this activity strengthened social bonds and religious culture within the community through active participation of various stakeholders. Thus, the Qira’ah Seven Tones training proved effective not only as a medium for improving technical skills, but also as an instrument of da’wah, character education, and the preservation of valuable local religious traditions.